Risk factors for low resilience among Grade 10 adolescents in the Gampaha district, Sri Lanka: a case-control study - Pavithra Godamunne; Shamila Manori; Pushpa Lalani Jayawardana (BMJ Public Health)
Objective Resilience means the ability to deal successfully with difficult situations, and hence low resilience will lead to many negative outcomes. The aim of this study was to explore risk factors for low resilience among Grade 10 adolescents in Gampaha district, Sri Lanka.Methods Resilience levels and data related to putative risk factors were obtained by using a validated 14-Item Sinhala Resilience Scale and a questionnaire on putative risk factors (both of which were self-administered) from Grade 10 adolescents by conducting a descriptive cross-sectional study. There were 464 (33.6%) cases with low resilience (score=14–73) and 916 (66.4%) controls with high resilience (score=74–98). For the case-control study, the computed sample size for each case and control group was 128, who were selected by applying simple random sampling. Risk factors for low resilience were determined using bivariate and multivariable analyses by applying χ2 test and multivariable logistic regression. Results were expressed as ORs with respective 95% CIs.Results Among the 33 putative risk factors analysed, 13 were found to be significant in bivariate analysis. In multivariable logistic regression analysis, out of 24 independent variables entered initially into the model, only 9 were retained in the final model. These comprised (1) one or both parents dead (AOR=2.5, 95% CI [1.2, 14.5]; p=0.032), (2) mother’s low educational level (AOR=1.9, 95% CI [1.6, 3.8]; p=0.021), (3) sleep <8 hours (AOR=1.6, 95% CI [1.1, 3.8]; p=0.002), (4) having less than six close classmates (AOR=1.5, 95% CI [1.1, 4.3]; p=0.021), (5) not attending Sunday school (AOR=1.8, 95% CI [1.1, 10.6]; p=0.001), (6) being short-tempered (AOR=2.2, 95% CI [1.5, 3.6]; p=0.003), (7) having conflicts with friends (AOR=1.4, 95% CI [1.2, 7.5]; p=0.043), (8) not seeking help when confronted/facing with difficulties (AOR=1.6, 95% CI [1.2, 6.9]; p=0.032) and (9) lack of support from home when in need (AOR=1.6, 95% CI [1.2, 5.8]; p=0.001).Conclusion and recommendation Altogether nine risk factors were identified. Interventions focusing on risk factors ascertained should be developed and conducted regularly by the schools, targeting all adolescents of Grade 10 to boost their status of resiliency.